Benefits and negatives of corticosteroid therapy in corneal patients - Zemanová, Markéta; Matušková, Veronika (Czech and Slovak Ophthalmology, 2017)
Introduction: Corticosteroid therapy is very beneficial in many types of eye diseases. Corticosteroids are used in the treatment of inflammatory and immunological diseases of the eye. Purpose: The aim is to present basic informations about effects of steroids in tissues, their side effects and treatment strategy. Methods and results: Authors process overview of local and systemic steroids and their dosage forms. They refer to the most common problems associated with corticosteroid therapy. Conclusion: Although corticosteroids include medicine across to one of the most frequently prescribed drugs at all, it is always necessary to treat very carefully indicate any corticosteroid preparation and prior to its administration to eliminate all infectious diseases, take a thorough anamnesis and complete examine the patient.
Keywords: rohovka; Corneal Diseases; Humans; hormony kůry nadledvin; nemoci rohovky; Adrenal Cortex Hormones; Cornea; lidé